Association between Laryngeal Pepsin Levels and the Presence of Vocal Fold Polyps. (January 2017) - Wang, Lu; Tan, Jia-Jie; Wu, Ting; Zhang, Rui; Wu, Jia-Nuan; Zeng, Fang-Fang; Liu, You-Li; Han, Xiao-Yan; Li, Yan-Fei; Li, Xiang-Ping
Objective: To determine whether pepsin, the main component of refluxed gastric contents, is significantly associated with vocal fold polyps and to evaluate the diagnostic value of pepsin in vocal fold polyps' tissues. Study Design: Cross-sectional study. Setting: Nanfang Hospital of Southern Medical University. Subjects and Methods: The study included 32 patients with vocal fold polyps and 16 healthy controls between 2011 and 2012. Reflux symptom index and reflux finding score assessments, 24-hour combined multichannel intraluminal impedance and pH monitoring, and biopsy of the vocal fold polyp tissues or posterior laryngeal mucosa (healthy controls) for immunohistochemical pepsin staining were performed. Results: The expression of pepsin was significantly higher in patients with vocal fold polyps than in controls (28/32, 75% vs 5/16, 31.25%; P < .001). The pepsin levels were significantly positively correlated with upright position pharyngeal acid reflux and esophageal reflux parameters adjusted by age. Based on pepsin staining data, the sensitivity and negative predictive values of 24-hour pH monitoring, the reflux symptom index, and the reflux finding score were 70% to 84.62%, whereas their specificity and positive predictive values were relatively low (20%-31.58%). Conclusion: Pepsin reflux may be a risk factor for vocal fold polyps formation. In addition, pepsin immunohistochemical analysis of polyp biopsy samples appears to be a more sensitive and effective test for diagnosing laryngopharyngeal reflux than the reflux symptom index, the reflux finding score, and 24-hour pH monitoring in a clinical setting.